Implementasi Pendidikan Multikultural di Era Revolusi 4.0: Implementasi Pendidikan Multikultural di Era Revolusi 4.0 - Koko Adya Winata (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2020)
This paper examines and describes the implementation of multicultural education components in the 4.0 revolution era. Multicultural Education provides an understanding of various types of educational activities as an integral part of universal culture. Multicultural education emphasizes a philosophy of cultural pluralism into the education system based on the principles of equality, mutual respect, tolerance, acceptance and understanding. Tolerance in diversity and moral commitment to social justice. Multicultural Education is perceived as an endeavor to achieve the shared life of diverse and heterogeneous human beings in an era of globalization which is full of new challenges. Through multicultural education, students are taught that diversity is a necessity that must be maintained and maintained. The components of multicultural education are directly related to learning objectives, materials, methods, media and evaluations that explain to students about the phenomenon of diversity. The component must be prepared in the implementation of multicultural education that will provide understanding to students such as gender, religion, social, ethnic and urban society. By using qualitative research methods researchers can explain and analyze how the implementation of multicultural education components in the 4.0 revolution era. Keywords: Multicultural Components Educational Implementation, Revolutionary Era 4.0